Opportunities and challenges to energy development on a ranch in western Colorado - developing a model for conservation and mixed use - Stewart, Scott, speaker; Belinda, Steve, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The High Lonesome Ranch (HLR) is a privately owned ranch of 38,000 deed acres and an additional 205,000 acres of leased public land in western Colorado. In 2011 the HLR and the Theodore Roosevelt Conservation Partnership (TRCP) entered into an agreement to work together towards a model approach to how energy development can be planned and implemented at landscape level to achieve a better balance between energy and other values. Though the implementation of the TRCP's 'FACTS for Fish and Wildlife' recommendations and working with stakeholders under a process that identifies and plans for current and future needs for everyone, we believe that the conflict that exists in many other areas can be reduced or eliminated. Plans are developed and implemented for landscapes not projects or individual wells and through mitigation (Avoidance, minimization and compensation) a 'net conservation benefit' can be achieved while producing energy resources. HLR is also employing the use of conservation tools through federal and state agencies for the management of focal species (sage grouse, mule deer) and be the first ranch in Colorado to have a Candidate Conservation Agreement with Assurances for greater sage grouse that addresses all threats to the species. HLR believes it is their responsibility to manage energy and wildlife to benefit all current and future needs with a proactive approach that prevents conflict on the entire 400 square mile landscape.
The High Lonesome Ranch: a model for responsible energy development at the landscape level
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses